2017
DOI: 10.1155/2017/1859167
|View full text |Cite
|
Sign up to set email alerts
|

Wear Characteristics of the Material Specimen and Method of Predicting Wear in Floating Spline Couplings of Aero-Engine

Abstract: In order to reduce wear and design high-performance spline coupling, the friction coefficient, wear coefficient, and wear depth of 14 groups of material specimens were tested using multifunctional friction and wear tester. The effect of materials, loads, rotation speed, and surface treatment on friction coefficient, wear coefficient, and wear depth was investigated. A method using an Archard's equation based on the finite element method to calculate the wear depth of 14 groups of material specimens was propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In this test, the rack-plane spline couplings were composed of 18CrNi4A steel, in accordance with Xue et al 16 The thickness of the carburized layer was 0.6-0.7 mm, and the surface hardness was 56.3 on the Rockwell C Hardness scale. The dimensions and structures of the specimens are shown in Figure 2(a) to (c).…”
Section: Experimental Arrangement and Specimensmentioning
confidence: 85%
See 1 more Smart Citation
“…In this test, the rack-plane spline couplings were composed of 18CrNi4A steel, in accordance with Xue et al 16 The thickness of the carburized layer was 0.6-0.7 mm, and the surface hardness was 56.3 on the Rockwell C Hardness scale. The dimensions and structures of the specimens are shown in Figure 2(a) to (c).…”
Section: Experimental Arrangement and Specimensmentioning
confidence: 85%
“…However, a slight upward trend still occurs, which is also caused by the temperature increase during the wear process. It can be noted from the Xue et al 16 that after carburization, 18CrNi4A has a dynamic friction coefficient of 0.12 with oil lubrication. Finally, it can be concluded that regardless of lubrication or no lubrication, the fretting friction coefficients on the surface of the spline couplings fluctuate between the dynamic friction coefficients and the static friction coefficients.…”
Section: Experimental Cases and Principlesmentioning
confidence: 99%
“…5 Therefore, while designing a coupling, a full nonlinear dynamic response analysis is a crucial step taken to determine the vibration effects accurately, control the fretting, reduce wear, and prevent spine's failure, respectively. 6,7 Many studies incorporate the nonlinear dynamic response of the aviationinvolute splines. [8][9][10] Roger et al and Walton et al determined the influence of the external force and frequency on the angular stiffness and damping coefficient of axial spline couplings in high-speed rotating machinery.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] And from the calculation formula of fretting wear, it can be seen that the wear coefficient, relative slide distance, and contact stress are all the basic parameters for the calculation of fretting wear. [4][5][6] The relative slide distance is a combination of the slide distance between the friction surfaces of two spline couplings and their vibration displacement under fluctuating loads. 5,6 However, the relative slide distance and the contact stress of involute spline coupling must be calculated based on the dynamic force between spline teeth.…”
Section: Introductionmentioning
confidence: 99%